2013
DOI: 10.1074/jbc.m113.471268
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cytokines Induce a Unique Mineralizing Phenotype in Mesenchymal Stem Cells Derived from Human Bone Marrow

Abstract: Background:The effects of inflammation upon the biology of human mesenchymal stem cells are poorly understood. Results: IL-1␤ provoked massive hydroxyapatite deposition by inhibiting ectonucleotide pyrophosphatase. Cells did not express typical markers of osteoblasts or other mesenchymal lineages. Conclusion: Inflammation promotes mineralization by a novel mechanism. Significance: These data provide new insights into cytokine effects on mineralization of soft tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 36 publications
4
46
0
Order By: Relevance
“…This agrees with the work of Ferreira et al 17 in which low levels of IL-1 β and TNF- α induced mesenchymal stem cells to differentiate into osteoblasts independent from the NF- κ B signaling pathway. Higher levels of IL-1 β and TNF- α can enhance osteoclastogenesis by direct stimulation of macrophages and osteoclasts.…”
Section: Discussionsupporting
confidence: 93%
“…This agrees with the work of Ferreira et al 17 in which low levels of IL-1 β and TNF- α induced mesenchymal stem cells to differentiate into osteoblasts independent from the NF- κ B signaling pathway. Higher levels of IL-1 β and TNF- α can enhance osteoclastogenesis by direct stimulation of macrophages and osteoclasts.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, analysis of the extracellular vesicles produced by IL-1β treated mesenchymal stem cells showed a clearly altered ratio of ENPP1 to alkaline phosphatase and less PPi in the vesicle fraction. This work supports the hypothesis that inflammatory cytokines can induce mineralization by altering the enzymes regulating the PPi/Pi ratio on extracellular vesicles [21]. …”
Section: Factors Regulating Articular Cartilage Vesicle Mineralizationsupporting
confidence: 89%
“…For example, bone marrow-derived mesenchymal stem cells undergo massive mineralization in response to interleukin-1β (Il-1β). Interesting work exploring the mechanism of this effect demonstrated that mesenchymal stem cells do not undergo osteoblastic differentiation in response to IL-1β [21]. Instead, mineralization correlated with a decrease in cellular levels of ENPP1.…”
Section: Factors Regulating Articular Cartilage Vesicle Mineralizationmentioning
confidence: 99%
“…These factors are particularly important for regulating stem cell activities such as mobilization, proliferation, and differentiation. 20,21,[25][26][27][28] More importantly, some of these signals are only transiently activated at the early stage of injury and usually diminish by day 10 after injury. 7,20,21,25,29 In the present study, we have demonstrated that there was limited blood chimerism 3 days after parabiotic surgery, and that the crosscirculatory system required 7 to 10 days to be fully established.…”
Section: Discussionmentioning
confidence: 99%